Electronic Literature: Affiliations, Communities, Translations - Torres, Rui (2019)
The ELO (Electronic Literature Organization) organized its 2017 Conference, Festival and Exhibits, from July 18-22, at University Fernando Pessoa, Porto, as well as several other venues located in the center of the historic city of Porto, Portugal. Titled Electronic Literature: Affiliations, Communities, Translations, ELO’17 proposes a reflection about dialogues and untold histories of electronic literature, providing a space for discussion about what exchanges, negotiations, and movements we can track in the field of electronic literature. The three threads (Affiliations, Communities, Translations) weave through the Conference, Festival and Exhibits, structuring dialogue, debate, performances, presentations, and exhibits. The threads are meant as provocations, enabling constraints, and aim at forming a diagram of electronic literature today and expanding awareness of the history and diversity of the field. Our goal is to contribute to displacing and resituating accepted views and histories of electronic literature, in order to construct a larger and more expansive field, to map discontinuous textual relations across histories and forms, and to create productive and poetic apparatuses from unexpected combinations.